A Tribute to Robert Jahn - Dobyns, York (Journal of Scientific Exploration, 2018)
By now the story of the PEAR lab's founding has been told many times, but it has been long enough since Bob Jahn retired that there may be readers who don't know it. In the 1970s, Dean Jahn of the Princeton University School of Engineering and Applied Sciences made a speech welcoming freshmen to the engineering program, in which he promised that if they did good work and maintained a good academic standing, they could do their senior thesis (a major project required for graduation at Princeton) on any topic they wished. Three years later a student held him to that promise. That student wanted to do a senior thesis on replicating Helmut Schmidt's experiments in psychokinesis — experiments that had produced positive results. No faculty member was willing to serve as an advisor for such a thesis. So Dean Jahn honored his word and served as this student's thesis advisor himself. Somewhat to his own surprise, the student's apparatus broadly replicated Schmidt's results: an electronic noise generator showed shifts in its output distribution in accordance with human intention. The student graduated, but Dean Jahn decided he couldn't leave matters standing thus. The phenomenon needed deeper investigation. He went searching for somebody with a background more oriented to this field of research in which he was himself a novice, and found Brenda Dunne; together the two of them founded the Princeton Engineering Anomalies Research program — PEAR. Bob's interest in this research field was not conjured up by a single anomalous result in a student experiment. Not yet 50, he had arguably reached the pinnacle of his chosen profession. He was in charge of the School of Engineering at one of the most prestigous universities in America — his own beloved alma mater, no less — and had established a highly successful Electric Propulsion Laboratory already doing groundbreaking research for NASA. It was hard to see how he could advance further along the same track, save by moving inexorably into administration rather than actually doing science. Like Alexander but more pragmatic, he was already pondering what other scientific worlds there might be for him to conquer when the student's experiment pointed at an area that seemed ripe for rigorous, systematic investigation.